Asymmetric Reduction of Trifluoromethyl Alkynyl Ketimines by Chiral Phosphoric Acid and Benzothiazoline - Miyagawa, Masamichi; Takashima, Kensuke; Akiyama, Takahiko (Synlett, 2018)
An enantioselective transfer hydrogenation reaction of alkynyl ketimine bearing a trifluoromethyl group was accomplished. Chemoselective reduction of ketimine was achieved by the combined use of chiral phosphoric acid and benzothiazoline to give α-trifluoromethyl propargylamine in good to high yields and with excellent enantioselectivity.
Keywords: alkynyl ketimine; chiral phosphoric acid; benzothiazoline; asymmetric transfer hydrogenation reaction; trifluoromethyl group